Consumers' perceptions on GM food safety in urban China - Ji-kun HUANG; Bo-wen PENG (Journal of Integrative Agriculture)
The debate about the safety of genetically modified (GM) food has attracted public attention in concurrence with the rapid development of agricultural biotechnology. This paper examines the consumers' perceptions on the safety of GM food in China. Based on a unique survey dataset, this study shows that consumers in urban China have significantly changed their perceptions on GM food safety. The percentage of consumers who perceived such food as unsafe for consumption increased by more than 30% in the 2002–2012 period. Approximately half of the consumers did not have an opinion on this issue. Major shifts have been occurred after 2010, likely because of the increasing influence of negative media reports on GM technology in recent years. Several individual and household's characteristics are shown to significantly affect consumers' perceptions on GM food safety, such as gender, education, food allergy experience and resident city size. The paper concludes with policy implications.